Colorimetric determination of iron in beer by flow injection analysis using - Fernandes, Sílvia M. V. (2011)
A flow injection analysis system with colorimetric detection for the iron determination in beer is described. The methodology is based on the formation of a complex produced by the reaction of iron (II) with 1,10-phenanthroline, after reduction of iron (III) to iron (II) by ascorbic acid. The asymmetric merging zones technique was used to allow the sequential blank and sample absorbance readings. The results obtained with the developed system were in good agreement with those provided by the reference method (relative deviations lower than 4%) and exhibited a precision (relative standard deviation) better than 7%. A sampling-rate of 60 determinations per hour can be achieved.